Wykorzystanie budek lęgowych na siedliskach borowych w Puszczy Augustowskiej - Zawadzki, Grzegorz; Sołtys, Anna; Zawadzka, Dorota; Zawadzki, Jerzy (Leśne Prace Badawcze, 2019)
In 2011–2014, the occupancy of nest-boxes by secondary hole-nesting birds and their breeding success was investigated in pine stands of the Augustów Forest (North-Eastern Poland). In the studied area of 12600 ha, the share of Scots Pine Pinus sylvestris L. in the stands was 92%. On average, birds occupied 54% and bats 3% of the 224–317 nest boxes controlled yearly. Nest boxes were also used by the Pygmy Owl Glaucidium passerinum L. as food caches. In total, broods of nine secondary hole-nesting species were observed, but only four bird species nested in each year of study. The most numerous species, occupying 53–60% of all boxes each year was the Pied Flycatcher Ficedula hypoleuca Pall. The Great Tit Parus major L. occupied 15–24% and the Coal Tit Periparus ater L. 10–12% of available nest-boxes, while the Redstart Phoenicurus phoenicurus L. used 2–7% of nest boxes. The yearly breeding success was highest for tits (Great Tit – 52–84%, Coal Tit – 50–72%) and strongly variable for the Pied Flycatchers – 38–78%. Broods were lost due to predation by martens Martes sp. (38%) and great spotted woodpeckers Dendrocopos major L. (6%) as well as nest competition (2%). The nest-boxes were occupied at a constant rate during the following four years after their exposition. Over 67% of the new nest-boxes were occupied annually which means new nest-boxes (up to 4 years) were occupied significantly more often than boxes older than 4 years.